THE EFFECT OF EXCHANGE RATE FLUCTUATIONS ON BALI TOURISM SECTOR - Nugroho, Ignatius Adhi; Gunawan, Stephanie; Awirya, Agni Alam; Nurman, Putriana (Jurnal Ekonomi dan Pembangunan, 2017)
Trade, hotel, and restaurant sector which represents tourism sector is the biggest contributor for Bali economy sector. It accounts for more than 30% of Bali income. Most of the income comes from foreign tourists’ expenditure which accounts for more than half of the local tourists’ with the foreign tourists’ arrival of 36% more of the locals’. The fact therefore underlines the importance of foreign tourist growth observation due to its significance for Bali economy. This research aims at estimating the change of tourists’ arrival because of the fluctuation of rupiah (depreciation and appreciation) which allegedly thought as one of the underlying factors affecting the number of tourists’ arrival. This research also aims at analyzing the sensitivity of foreign tourists’ to the change of traveling cost and at analyzing the tourists’ destination shift should there be any change of traveling cost and also at analyzing the characteristics of the foreign tourists affected by the exchange rate fluctuations. Event studies shows that exchange rate fluctuation does not affect foreign tourists’ decision on coming to Bali. This is due to the fact that foreign tourists’ arrival escalates regardless the exchange rate fluctuation (depreciation and appreciation). Meanwhile, descriptive analysis shows that only minority of foreign tourists are affected by exchange rate fluctuations with underlying characteristic of the country of origin. Moreover, despite the rise of traveling cost to Bali, more than 50% respondents choose to travel to Bali and although there is a change of destination, more than 30% respondents choose other Asian countries as a replacement. It is also revealed that the older the tourists, the less the effect of exchange rate fluctuation on their decision to visit Bali.